Tinjauan Yuridis Pelindungan Hukum Pekerja Migran Indonesia - Ade Savirah Mahmud; Hasbuddin Khalid; Muhammad Rinaldy Bima (Qawanin Jurnal Ilmu Hukum, 2020)
Abstract This research aims to understand and know the legal protection procedures of Indonesian Migrant Workers and the obstacles that often occur in the Indonesian Migrant Workers Protection Agency Makassar Region, to answer the formulation of problems in this study, used a type of empirical research. This research aims to understand and know the legal protection procedures of Indonesian Migrant Workers and the obstacles that often occur in the Indonesian Migrant Workers Protection Agency Makassar Region, to answer the formulation of problems in this study, used a type of empirical research. Based on the results of research comparing Indonesian migrant workers that the legal protection procedures of Indonesian migrant workers conducted at the BP2MI office from before work, during work, and after work. Based on the results of research comparing Indonesian migrant workers that the legal protection procedures of Indonesian migrant workers conducted at the BP2MI office from before work, during work, and after work. The obstacles faced by the Indonesian Migrant Workers Protection Agency are many illegal workers who are difficult to track by the government, touts that are difficult to eliminate and not serious about the government in protecting Indonesian workers abroad. Abstrak Penelitian ini bertujuan untuk memahami dan mengetahui prosedur pelindungan hukum Pekerja migran Indonesia dan hambatan-hambatan yang sering terjadi pada Badan Pelindungan Pekerja Migran Indonesia Wilayah Makassar, untuk menjawab rumusan masalah pada penelitian ini, digunakan jenis penelitian empiris.Berdasarkan hasil penelitian pelindngan Pekerja Migran Indonesia bahwa prosedur pelindungan hukum pekerja migran indonesia yang dilakukan pada kantor BP2MI dari sebelum kerja, saat kerja, dan setelah kerja. Hambatan-hambatan yang dihadapi Badan PerlindunganPekerja Migran Indonesia yaitu banyak pekerja illegal yang sulit terlacak oleh pemerintah, calo yang sulit untuk dihilangkan dan tidak seriusnya pemerintah dalam melindungi pekerja indonesia di luar negeri.